Collier barbecue at Black Berry Farm - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panoramic view showing the attendees of the 1957 Collier Black Berry Farm, gathered outdoors. In the center of the image, a sign, held by several members of the large group, reads "8th Annual Collier Barbeque."